Les quatre premiers livres de La Franciade (1572) - Ronsard, Pierre de 1524-1585 (Droz, 2023)
Remaining unfinished, at the end of a long gestation, after the publication of its first four books and for a long time unloved by Ronsard scholars, La Franciade is today perceived more positively, re-evaluated if not rehabilitated, as attested for forty years. years the growing number of studies of which it is the subject. We are far from Sainte-Beuve who did not quote a single line. Not only does it conceal poetic riches that cannot be found elsewhere, but it also appears as the indispensable sounding board for the epic fragments scattered throughout the work. Our edition, based on the original of 1572, gives the many variants, manuscripts (including those of Book IV which was long believed to have been destroyed in the fire of the Turin library) and printed (from the two reissues of the following year to the Posthumous Works of 1587), and reproduced in the appendix, among other texts , the important last preface "touching the Heroic Poem". An invitation to rediscover La Franciade with new eyes
Keywords: Quelle; Kommentar